Pemberdayaan Perempuan Melalui Pelatihan Menjahit di Desa Sukosono Jepara - Hadi Putra Hardiyanto; Azzah Nor Laila; Lutfiyanti Axmi Reza; Desi Maila Fira (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2021)
The Covid-19 pandemic has an impact on the weak economy of families, many workers have been laid off, and businesses are not running optimally. On the other hand, the group of mothers has free time, the potential to be productive independently by working from home, but they do not have the skills. So to overcome these problems the service team carried out sewing training service activities. This service activity aims to empower women, increase creativity, and independence of women in Sukosono, Kedung, Jepara.. This service method is socialization, training, and sewing assistance which includes pattern making, cutting and sewing. This service activity is carried out face-to-face or offline while adhering to health protocols. Sewing training is carried out in several stages. First, participants are trained to make patterns using cardboard paper and then apply them to the fabric. Second, participants are taught to cut cloth properly. Third, participants are trained to sew with the correct technique, so that the results are neat. The fabric used is Troso woven cloth, so that participants will be able to use Jepara's local products. The response of the participants to this dedication showed that in the material aspect 95% considered it very good, 90% of the facilitator aspect considered it very good, and the rest responded well. The results of this dedication showed that 85% of the participants were successful in sewing skills, seen from the success of the participants in making a sewing service business start-up and convection from fabric after participating in service activities.